The relationship between self-reported mental health and redeemed prescriptions of antidepressants: a register-based cohort study. Issue 1 (December 2016) - Frandsen, Louise; Villumsen, Line; Hjorth, Cathrine; Nielsen, Berit; Ullits, Line; Torp-Pedersen, Christian; Bøggild, Henrik; Overgaard, Charlotte
Abstract Background Poor mental health is a major problem in most western societies, especially predominant among young adults. However, associations of self-reported poor mental health with subsequent psychiatric or medical treatment are unknown. We examined the relation between self-reported mental health and redeeming prescriptions of antidepressants among three age groups. Methods We analyzed data from 16, 233 individuals aged 16 years and over randomly selected to participate in the 2010 North Denmark Region Health Survey completed in February 2010. Mental health was defined according to the Short-Form 12 instrument (SF-12) and dichotomized into poor and good. Outcome data were retrieved from administrative information on redeemed prescriptions of antidepressants between February 2010 and December 2012. Crude cumulative incidence curves were produced to illustrate the probability of redeeming new prescriptions of antidepressants over time. Cox regression analysis was used to estimate risk of redeeming prescriptions of antidepressants when having poor mental health, adjusted for preselected explanatory covariates. Results Among the young (16–29 years-old), 620 (23 %) participants suffered from poor mental health. Among the adults (30–59 years-old) and elderly (60 years-old or over), 1592 (18 %) participants and 723 (15 %) reported poor mental health, respectively. Overall, women were more likely than men to rate their mental health as poor. For all age groups, there was an increased probability for redeeming prescriptions of antidepressants when having poor mental health. The hazard ratio [HR] for redeeming prescriptions of antidepressants for those reporting poor versus good mental health, adjusted for sex, ethnicity, marital status, education level, occupational status, smoking and physical activity was 3.1 (95 % confidence interval [CI] 2.20–4.29) for young participants. For adults, the HR was 2.3 (95 % CI 1.86–2.78) and for elderly, it was 3.5 (95 % CI 2.66–4.57). Conclusion Self-reported poor mental health was more frequent among younger than older participants. Overall, antidepressants were the most often used treatment. An increased probability of redeeming antidepressant prescriptions when having self-reported poor mental health was observed in all age groups. These findings suggest that frequent reporting of poor mental health is a common issue for all age groups that needs more attention.